Incidence and recurrence of large forest fires in mainland Portugal - Ferreira-Leite, F. (2016)
Fires are an important land use tool, a growing global hazard, and a factor involved in landscape processes with feedbacks on land degradation, especially in the Southwestern Mediterranean Europe, where the importance of fires in shaping ecological processes has long been recognized. As fires become recurrent, their intensity and dimension have increased and they have taken on catastrophic proportions, losing their role as catalysts of ecosystem renewal. Fires, and especially large forest fires (LFF), are the main drivers of land degradation in forest areas in Mediterranean sub-humid regions and are likely to increase as a result of climate and other global changes. The study area consists of the whole of mainland Portugal, which for the purpose of civil protection, is divided into 18 districts. The data used, including physical and demographic characteristics, change in land use and land cover, and economic structures are provided mainly by the Institute for the Conservation of Nature and Forests in statistical format and in shapefile format. Throughout the years, LFF in Portugal have become increasingly important. Although LFF in mainland Portugal represent a small fraction of the total occurrences (0.8 %), in accordance with the trends of the Mediterranean Basin, they are responsible for a large percentage of burned areas ([70 %). With the use of the GIS software, we were able to use the available information to generate a map of forest fire recurrences and, with the purpose of detecting homogeneous groups between the districts of mainland Portugal, a cluster analysis was applied. Using a multiple regression analysis, we present the LFF and their recurrence in mainland Portugal at the district level, demonstrating their regional incidence and the similarity between districts.